International medium-term business cycles - Dominik Hirschbühl; Martin Spitzer (European Central Bank (ECB), 2021)
Foreign driven medium-term oscillations that originate from uctuations in technological frontier countries gained widespread attention among policymakers. To study this phenomenon in the context of domestic and other foreign drivers of the euro area business cycle, we develop a medium-scale, two-economy dynamic stochastic general equilibrium model with endogenous growth and estimate it with Bayesian methods for the United States and the euro area for the period from 1984:Q1 to 2017:Q4. The framework suggests that foreign shocks can be a substantial source of medium-term oscillations that contribute to pro-cyclicality of real GDP across countries. Notably, US shocks to liquidity preference and trade demand explain more than a third of the euro area downturn during the Great Recession.
Keywords: E2; E5; F1; F4; O4; 330; Two-economy DSGE; endogenous growth; R&D; resilience; Bayesian estimation